2018
DOI: 10.1016/j.ijrobp.2018.04.077
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Comparison of CT-Based Surrogates of Lung Ventilation With Hyperpolarized Helium-3 and Xenon-129 Gas MRI in Patients Undergoing Radiation Therapy

Abstract: Spatial comparison of CT-based surrogates of lung ventilation with hyperpolarized Helium-3 and Xenon-129 gas MRI in patients undergoing radiation therapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 56 publications
0
50
0
Order By: Relevance
“…Comparisons with Xenon CT in mechanically ventilated sheep, and ex vivo imaging of fluorescent microspheres in mice have featured highly controlled experimental conditions and achieved strong cross‐modality correlations (e.g., with voxel‐level correlations exceeding ∼0.8 for small lung subvolumes). In contrast, clinical human studies using single photon emission computed tomography (SPECT) with technetium‐99m (99mTc), positron emission tomography (PET) with gallium‐68 (68Ga),, and hyperpolarized gas MRI with either helium‐3 (3He) or xenon‐129 (129Xe) have all shown variable cross‐modality correlations (mean Spearman correlations in the range 0.1–0.8), which has been variously attributed to poor image quality in the 4DCT dataset or the RefVI scan, time delays between intrapatient scans, or poor reproducibility of breathing patterns/maneuvers. A recent study by Eslick et al .…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons with Xenon CT in mechanically ventilated sheep, and ex vivo imaging of fluorescent microspheres in mice have featured highly controlled experimental conditions and achieved strong cross‐modality correlations (e.g., with voxel‐level correlations exceeding ∼0.8 for small lung subvolumes). In contrast, clinical human studies using single photon emission computed tomography (SPECT) with technetium‐99m (99mTc), positron emission tomography (PET) with gallium‐68 (68Ga),, and hyperpolarized gas MRI with either helium‐3 (3He) or xenon‐129 (129Xe) have all shown variable cross‐modality correlations (mean Spearman correlations in the range 0.1–0.8), which has been variously attributed to poor image quality in the 4DCT dataset or the RefVI scan, time delays between intrapatient scans, or poor reproducibility of breathing patterns/maneuvers. A recent study by Eslick et al .…”
Section: Introductionmentioning
confidence: 99%
“…The percentage ventilated volume (%VV) was calculated for each patient by taking the ratio of the binary lung segmentations of 3 He and 1 H MRI. For spatial comparison of 3 He MRI and CT ventilation, for each patient, MR images were registered to the TLC-CT image's spatial domain via the anatomical same-breath 1 H MRI as previously described (Tahir et al, 2014) and Dice similarity coefficients (DSCs) were computed separately for the binary segmentations of both CT ventilation percentiles with that of FRC+1L and TLC He MRI. The workflow for the comparison method of FRC+1L and TLC 3 He MRI with CT ventilation is shown in Figure 1.…”
Section: Comparison Of 3 He Mri and Ctmentioning
confidence: 99%
“…Whilst we can say that CT ventilation derived from TLC and FRC may not provide measures of ventilation which are as sensitive as FRC+1L 3 He MRI at depicting ventilation defects, we cannot say that this will be the case for CT ventilation derived from a different pair of inflation levels. For example, we recently demonstrated that CT ventilation maps derived from FRC and FRC+1L show moderate correlations with hyperpolarised gas MRI and marked ventilation defects (Tahir et al, 2018). To comprehensively answer this question, we require CT acquired at more than two inflation levels (e.g.…”
Section: Impact Of 3 He Mr Inflation Level On Correlation With Ct Venmentioning
confidence: 99%
See 2 more Smart Citations